Employee Motivation Strategies and Sales Performance: A Case Study of Hawk’s Eye Lodge Bunyonyi. - Kihembo, Linnet (Kabale University, 2024)
The study was bout employee motivation strategies and sales performance. A case study of Hawk’s Eye Lodge Bunyonyi following the study objectives which were; to identify employee motivation challenges in Hawk’s Eye Lodge Bunyonyi Kabale District, to identify employee motivation strategies in Hawk’s Eye Lodge Bunyonyi Kabale District and to assess the level of sales performance in Hawk’s eye lodge Bunyonyi Kabale District. The study employed descriptive research design across a sample of 50 respondents and data collection tools such as interviews and questionnaires were used to collect data from the participants. The findings of the study were that the research emphasized the significance of creating a positive work environment characterized by open communication, teamwork, and supportive leadership. A supportive workplace culture fosters employee satisfaction and motivation, ultimately contributing to enhanced sales performance. Providing regular feedback and recognition to employees for their contributions was identified as a motivational factor. Acknowledging employee efforts and providing constructive feedback helps employees feel valued and engaged, leading to improved sales outcomes. The study concluded the case study demonstrates that effective employee motivation strategies are integral to achieving sales success at Hawk’s Eye Lodge Bunyonyi. By focusing on factors such as recognition, incentives, training, a positive work environment, feedback, goal alignment, and continuous improvement, the lodge was able to enhance employee motivation and drive sales performance. The study recommends developing a structured recognition program that acknowledges and rewards employees for their contributions to sales performance. This could include employee of the month awards, quarterly bonuses for top performers, or public recognition during team meetings.